Knee pain and osteoarthritis in older adults: a review of community burden and current use of primary health care. Issue 2 (1st February 2001) - Peat, G; McCarney, R; Croft, P
Abstract : BACKGROUND: Osteoarthritis is the single most common cause of disability in older adults, and most patients with the condition will be managed in the community and primary care. AIM: To discuss case definition of knee osteoarthritis for primary care and to summarise the burden of the condition in the community and related use of primary health care in the United Kingdom. DESIGN: Narrative review. METHOD: A literature search identified studies of incidence and prevalence of knee pain, disability, and radiographic osteoarthritis in the general population, and data related to primary care consultations. Findings from UK studies were summarised with reference to European and international studies. RESULTS: During a one year period 25% of people over 55 years have a persistent episode of knee pain, of whom about one in six in the UK and the Netherlands consult their general practitioner about it in the same time period. The prevalence of painful disabling knee osteoarthritis in people over 55 years is 10%, of whom one quarter are severely disabled. CONCLUSION: Knee osteoarthritis sufficiently severe to consider joint replacement represents a minority of all knee pain and disability suffered by older people. Healthcare provision in primary care needs to focus on this broader group to impact on community levels of pain and disability.